Circular polariser for use in a gyro‐travelling wave amplifier. Issue 11 (1st August 2013) - Robertson, Craig W.; Young, Alan R.; Ronald, Kevin; Cross, Adrian W.; Whyte, Colin G.
Abstract : A corrugated rectangular waveguide, commonly used in radio frequency antennas applications, was considered for use in a gyro‐TWA experiment. This waveguide transducer produced broadband circularly polarised radiation in the Ka‐band frequency range (26–40 GHz). Computer simulations, using computer simulation technology Microwave Studio ®, were carried out and predicted return losses exceeding 30 dB and a 6° phase variation for 20% bandwidth centred at 31 GHz. Comparison between experimental measurements and simulations showed good agreement. The performance of this polariser was also compared to that of a conventional elliptical converter. Owing to its broadband performance the authors consider some of the technical aspects of applying this component to a Ka‐band gyro‐TWA experiment.